MOF-activated carbon composite adsorbent as well as preparation method and application thereof

By synthesizing MOF-UiO-66-NH2 in situ on activated carbon, a MOF-activated carbon composite adsorbent was constructed, which solved the problem of insufficient directional selectivity of activated carbon, and achieved efficient adsorption of ethyl carbamate, maintaining food flavor and reducing costs.

CN119303552APending Publication Date: 2025-01-14LUZHOU LAOJIAO CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410871386.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-01
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Existing activated carbon lacks sufficient directional selectivity when adsorbing ethyl carbamate, which affects the flavor of food while removing ethyl carbamate.

Method used

MOF (UiO-66-NH2) was synthesized in situ in the pores and surface of activated carbon. The surface properties of activated carbon were adjusted by MOF to construct MOF-activated carbon composite adsorbent, thereby achieving directional and selective adsorption of ethyl carbamate.

Benefits of technology

It improves the adsorption capacity and selectivity of ethyl carbamate, maintains the flavor of food without affecting it, has a low cost, and has good prospects for engineering applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119303552A_ABST
    Figure CN119303552A_ABST
Patent Text Reader

Abstract

The invention discloses an MOF-activated carbon composite adsorbent as well as a preparation method and application thereof, and belongs to the technical field of brewed food adsorption materials. The preparation method of the MOF-activated carbon composite adsorbent comprises the following steps: performing in-situ synthesis on MOF in pores and the surface of activated carbon, and adjusting the surface property of the activated carbon through the MOF, so that the activated carbon is matched with ethyl carbamate while the crystal structure of the MOF is not damaged; and the directional selectivity and stronger adsorbability of the MOF-activated carbon composite adsorbent on ethyl carbamate are realized through the synergistic effect of the two. The MOF-activated carbon composite adsorbent disclosed by the invention is high in ethyl carbamate adsorption capacity, can be applied to brewed food production, is relatively low in price, has a good engineering application prospect, and can effectively solve the problem of insufficient directional selectivity of an existing activated carbon adsorption ethyl carbamate technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of brewed food adsorption materials, relates to the adsorption treatment of ethyl formate, and specifically relates to a MOF-activated carbon composite adsorbent and a preparation method and application thereof. Background Art

[0002] Ethyl carbamate (EC), also known as urethane, can be produced by the reaction of urea, citrulline and other precursors with ethanol. It is found in a variety of fermented foods, such as rice wine, wine, vinegar, and soy sauce. Ethyl carbamate has strong lung toxicity, gastric toxicity and strong carcinogenicity. It can be quickly absorbed from the intestines and skin. Long-term intake will significantly increase the incidence of various cancers. Ethyl carbamate is a multi-site carcinogen. In 2007, the International Agency for Research on Cancer (IARC) classified ethyl carbamate as a Class 2A carcinogen.

[0003] At present, strategies for reducing ethyl carbamate include chemical methods, enzymatic methods, metabolic process improvement methods and adsorption methods. Among them, the adsorption method has the advantages of simple operation, wide adaptability and strong processing capacity, and has become a control technology that has received extensive attention and research. The key to the adsorption method is to select an efficient adsorbent, among which activated carbon is the most widely used adsorbent in food production. The difficulty and key of the adsorption method lies in directional selectivity, that is, relatively specific removal of ethyl carbamate while maximally maintaining the normal taste and flavor of the food. Due to its wide pore size distribution, activated carbon will remove flavor substances in food while achieving the effect of reducing ethyl carbamate, which will have a certain impact on product quality, flavor and taste.

[0004] Metal-organic framework materials (MOFs) have excellent designability and modifiability due to their precisely defined crystal structure, adaptable pore environment, and good stability, making their adsorption process easily functionalized and adjustable. MOFs can also be combined with activated carbon to form new composite materials. Due to the coordination effect between MOFs and activated carbon, MOFs composite activated carbon materials not only inherit the advantages of MOF and activated carbon, but also can produce some new physical and chemical properties, thereby achieving selective and effective removal of ethyl carbamate in brewed foods. Summary of the invention

[0005] The technical problem to be solved by the present invention is the problem of insufficient directional selectivity of the existing activated carbon adsorption technology for ethyl formate.

[0006] The technical solution adopted by the present invention to solve the technical problem is as follows: in the first aspect, the present invention provides a method for preparing a MOF-activated carbon composite adsorbent: in situ synthesizing MOF in the pores and surface of activated carbon, adjusting the surface properties of activated carbon by MOF so that it matches ethyl formate without destroying the crystal structure of MOF, and achieving the directional selectivity and stronger adsorption of ethyl formate by the synergistic effect of the two; the MOF is UiO-66-NH 2 .

[0007] The preparation method of the above MOF-activated carbon composite adsorbent specifically comprises the following steps:

[0008] a. ZrCl 4 After mixing with DMF, the mixture is evenly dispersed by ultrasonication, and then activated carbon, water and benzoic acid are added and stirred evenly, and finally an organic ligand is added and stirred evenly again to obtain a mixed solution;

[0009] b. The mixed solution obtained in step a is subjected to a constant temperature reaction, and after the reaction is completed, it is cooled to room temperature, centrifuged, washed, and vacuum dried to obtain a MOF-activated carbon composite adsorbent.

[0010] Furthermore, in the above step a, ZrCl 4 The molar ratio to activated carbon is 1:30-130.

[0011] Furthermore, in the above step a, ZrCl 4 The molar ratio of , water, benzoic acid, organic ligand and DMF is 1:3:10:1:300.

[0012] Furthermore, the above-mentioned organic ligand includes terephthalic acid and 2-aminoterephthalic acid.

[0013] Furthermore, in the above step b, the isothermal reaction temperature is 80-140° C., and the reaction time is 12-36 h.

[0014] Furthermore, in the above step b, the solvent used for washing includes DMF, isopropanol and deionized water.

[0015] Furthermore, in the above step b, the vacuum drying temperature is 60-100°C.

[0016] In a second aspect, the present invention provides a MOF-activated carbon composite adsorbent for treating ethyl formate, which is prepared by the above-mentioned adsorbent preparation method.

[0017] In a third aspect, the present invention provides an application of the above-mentioned MOF-activated carbon composite adsorbent for treating ethyl formate in the production of brewed food.

[0018] The beneficial effects of the present invention are as follows: the preparation method of a MOF-activated carbon composite adsorbent for ethyl formate provided by the present invention is to synthesize MOF in situ in the pores and surface of activated carbon by a solvothermal method, adjust the surface properties of activated carbon by MOF to match ethyl formate, and construct a composite adsorption material with directional selectivity for ethyl formate through the complementary advantages and synergistic effect of the two. The prepared MOF-activated carbon composite adsorbent has a high adsorption capacity for ethyl formate and is relatively inexpensive, and has good prospects for engineering applications.

[0019] From the perspective of food, the MOF-activated carbon composite adsorbent for ethyl formate described in the present invention is based on commercial activated carbon. MOF has stable structural properties and has been proven to be used for water treatment and delivery of food active molecules. Therefore, the composite material is safe, reliable, environmentally friendly and green. In addition, the proportion of MOF in the composite material is low, and the resulting adsorption material is relatively cheap and cost-effective. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 (a) is the adsorption rate of ethyl formate in ethyl formate solution of the embodiments of the present invention and the comparative examples;

[0021] Figure 1 (b) is the adsorption rate of ethyl formate in the embodiment of the present invention and the comparative example in the simulated white vinegar solution;

[0022] Figure 1 (c) is the kinetic model of comparative example 1 of the present invention for ethyl carbamate in ethyl carbamate solution;

[0023] Figure 1 (d) is the kinetic model of Example 3 of the present invention for ethyl carbamate in ethyl carbamate solution;

[0024] Figure 2 The scanning electron microscope images of comparative example 1 and embodiment 3 of the present invention are shown;

[0025] Figure 3 The XRD diagrams of Comparative Example 2 and Example 3 of the present invention are shown below;

[0026] Figure 4 It is the adsorption selectivity coefficient of Examples 1 to 3 of the present invention and Comparative Examples 1 to 2. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings of the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] The technical solution of the present invention can be specifically implemented in the following manner.

[0029] In one aspect of the present invention, a method for preparing a MOF-activated carbon composite adsorbent is provided, comprising the following steps:

[0030] Step 1: ZrCl 4 Mix with DMF and disperse evenly by ultrasonication to obtain solution A;

[0031] Step 2: Add activated carbon, water and benzoic acid to the solution A obtained in step 1, stir evenly, and obtain a mixed solution B;

[0032] Step 3: Add the organic ligand to the mixed solution B obtained in step 2, and stir evenly to obtain a mixed solution C;

[0033] Step 4: subjecting the mixed solution C obtained in step 3 to a constant temperature reaction, cooling to room temperature after the reaction is completed, centrifuging, and discarding the supernatant to obtain a composite adsorption material;

[0034] Step 5: Wash and vacuum dry the composite adsorbent material obtained in step 4 to obtain a MOF-activated carbon composite adsorbent.

[0035] Furthermore, in step 2, ZrCl 4 The molar ratio to activated carbon is 1:30-130.

[0036] Furthermore, in step 3, ZrCl 4 The molar ratio of water, benzoic acid, organic ligand and DMF is 1:3:10:1:300. Furthermore, the organic ligand includes terephthalic acid and 2-aminoterephthalic acid.

[0037] Furthermore, in step 4, the reaction temperature is 80-140° C., and the reaction time is 12-36 h.

[0038] Furthermore, in step 5, the solvent used for washing includes DMF, isopropanol and deionized water; and the vacuum drying temperature is 60-100°C.

[0039] Another aspect of the present invention is to prepare a MOF-activated carbon composite adsorbent for treating ethyl formate by the above preparation method.

[0040] Another aspect of the present invention is to provide an application of the above-mentioned MOF-activated carbon composite adsorbent for treating ethyl formate in the production of brewed food.

[0041] The technical solution and effects of the present invention are further illustrated below through practical examples.

[0042] Example

[0043] 1. Preparation of adsorption materials

[0044] The present invention provides three groups of UiO-66-NH prepared by the preparation method of the MOF-activated carbon composite adsorbent of the present invention. 2 @AC adsorbent is used as Examples 1 to 3, and three groups of Comparative Examples 1 to 3, and the specific materials are shown in Table 1.

[0045] Table 1 Adsorption materials of the embodiments and comparative examples

[0046]

[0047] (1) Examples 1 to 3 were prepared by the following method:

[0048] ZrCl 4 After mixing with DMF and ultrasonic dissolving, add activated carbon and stir evenly, then add water and benzoic acid, and after it is completely dissolved, add 2-aminoterephthalic acid and stir evenly, transfer the uniform mixture to a 100mL polytetrafluoroethylene-lined stainless steel autoclave, and react at 120°C for 24h. After cooling to room temperature, the reaction solution is centrifuged and the precipitate is collected and washed three times with DMF and isopropanol respectively. After vacuum drying at 80°C for 12 hours, the adsorbent material UiO-66-NH 2 @AC-1. Among them, ZrCl 4 :H 2 O:benzoic acid:2-aminoterephthalic acid:DMF has a molar ratio of 1:3:10:1:300; wherein ZrCl in Example 1 4 The molar ratio of ZrCl in Example 2 is 1:33. 4 The molar ratio of ZrCl in Example 3 is 1:66. 4 The molar ratio of activated carbon is 1:100.

[0049] (2) Comparative Examples 1 to 3 were prepared by the following method:

[0050] Comparative Example 1: Untreated commercial activated carbon powder.

[0051] Comparative Example 2: Solvothermal method was used to convert ZrCl 4 After mixing with DMF and ultrasonic dissolving, water and benzoic acid were added. After they were completely dissolved, 2-aminoterephthalic acid was added and stirred evenly. The uniform mixture was transferred to a 100mL polytetrafluoroethylene-lined stainless steel autoclave and reacted at 120°C for 24h. After cooling to room temperature, the reaction solution was centrifuged and the precipitate was collected and washed three times with DMF and isopropanol respectively. After vacuum drying at 80°C for 12 hours, it was sealed and stored to obtain UiO-66-NH 2 Among them, ZrCl 4 :H 2 The molar ratio of O:benzoic acid:2-aminoterephthalic acid:DMF is 1:3:10:1:300.

[0052] Comparative Example 3: Solvothermal method was used to convert ZrCl 4 After mixing with DMF and ultrasonic dissolving, add activated carbon and stir evenly, then add water and benzoic acid, add terephthalic acid after it is completely dissolved and stir evenly, transfer the uniform mixture to a 100mL polytetrafluoroethylene-lined stainless steel autoclave, and react at 120°C for 24h. After cooling to room temperature, the reaction solution is centrifuged and the precipitate is collected and washed three times with DMF and isopropanol respectively. After vacuum drying at 80°C for 12 hours, the adsorbent material UiO-66@AC is obtained. Among them, ZrCl 4 :H 2 The molar ratio of O:benzoic acid:terephthalic acid:DMF is 1:3:10:1:300, ZrCl 4 : The molar ratio of activated carbon is 1:33.

[0053] 2. Performance Test

[0054] (1) Adsorption rate

[0055] Weigh equal amounts of the products prepared in Examples 1 to 3 and Comparative Examples 1 to 3, place them in centrifuge tubes, add equal amounts of ethyl carbamate solution and white vinegar simulation solution, place them in a shaker, shake them in a water bath for a certain period of time, calculate the concentration of ethyl carbamate in the solution before and after adsorption, and calculate the adsorption rate. Figure 1 As shown in (a) and (b).

[0056] Depend on Figure 1(a) and (b) show that the adsorption rate of ethyl carbamate by the MOF-activated carbon composite adsorbent of Examples 1 to 3 of the present invention is improved compared with the original MOF of Comparative Example 2. Taking Example 3 as an example, in the ethyl carbamate solution and the white vinegar simulation solution, the adsorption rate of Comparative Example 2 is 27.61% and 19.73%, respectively, while the adsorption rate of Example 3 is increased to 70.77% and 44.90%, which shows that MOF can increase its adsorption capacity and improve its ability to ethyl carbamate by compounding with activated carbon. And compared with UiO-66@AC of Comparative Example 3, it is found that UiO-66-NH 2 The adsorption rate of @AC is higher, which indicates that UiO-66-NH 2 @AC is more suitable for adsorbing ethyl carbamate.

[0057] (2) Kinetic model

[0058] Weigh equal amounts of Example 3 and Comparative Example 1 into a centrifuge tube, add ethyl carbamate solution, place in a shaker, and shake in a water bath for different times. Calculate the concentration of ethyl carbamate in the solution before and after adsorption, and calculate the adsorption rate. According to the effect of adsorption time on the removal effect of ethyl carbamate, calculate the kinetic model of the material for the removal of ethyl carbamate, such as Figure 1 As shown in (c) and (d).

[0059] Depend on Figure 1 (c) and (d) show that the adsorption of ethyl formate by activated carbon follows the pseudo-first-order kinetic model and the pseudo-second-order kinetic model (correlation coefficient R 2 0.9992 and 0.9997 respectively), UiO-66-NH 2 @AC-3 adsorption of ethyl carbamate follows a pseudo-second-order kinetic model (correlation coefficient R 2 are 0.7575 and 0.9955 respectively).

[0060] (3) Microscopic morphology

[0061] The microstructures of Comparative Example 1 and Example 3 were observed using a scanning electron microscope. Figure 2 The crystal structures of Comparative Example 2 and Example 3 were characterized by X-ray diffraction. The XRD patterns are shown in Figure 3 shown.

[0062] Depend on Figure 2 It can be seen that UiO-66-NH 2 The ions were successfully immobilized on activated carbon and evenly distributed.

[0063] Depend on Figure 3 It can be seen that the addition of activated carbon did not destroy the 2of the crystal structure.

[0064] (4) Directional selectivity

[0065] Weigh equal amounts of Examples 1 to 3 and Comparative Examples 1 to 2 in a centrifuge tube, add a white vinegar simulation solution, place in a shaker, shake in a water bath for a certain period of time, calculate the concentration of ethyl carbamate in the solution before and after adsorption, and calculate its adsorption rate for ethyl carbamate; calculate the concentration of organic acid in the solution before and after adsorption, and calculate its adsorption rate for organic acid; calculate the concentration of volatile substances in the solution before and after adsorption, and calculate its adsorption rate for volatile substances. Finally, the adsorption selectivity of the material for ethyl carbamate is calculated by the adsorption selectivity coefficient formula. The results are as follows: Figure 4 shown.

[0066] Depend on Figure 4 It can be seen from the adsorption data that the MOF-activated carbon composite adsorbents of Examples 1 to 3 have improved selective adsorption of ethyl carbamate compared to Comparative Examples 1 to 2. Taking Example 3 as an example, the selectivity coefficient for ethyl carbamate is increased by 67.00% to 6987.47% when volatile substances are used as a reference, and the selectivity coefficient for ethyl carbamate is increased by 265.69% to 4353.06% when organic acids are used as a reference. It can be seen that MOF can improve the directional selectivity for ethyl carbamate by compounding with activated carbon, and can achieve selective adsorption of ethyl carbamate.

[0067] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a MOF-activated carbon composite adsorbent, characterized in that: MOF is synthesized in situ in the pores and surface of activated carbon, and the surface properties of the activated carbon are adjusted by MOF to match ethyl carbamate without destroying the crystal structure of MOF. Through the synergistic effect of the two, the directional selectivity and stronger adsorption of ethyl carbamate by the MOF-activated carbon composite adsorbent are achieved; the MOF is UiO-66-NH2.

2. The method for preparing the MOF-activated carbon composite adsorbent according to claim 1, characterized in that: The steps include: a. ZrCl4 and DMF were mixed and dispersed evenly by ultrasound, and then activated carbon, water and benzoic acid were added and stirred evenly, and finally the organic ligand was added and stirred again to obtain a mixed solution; b. The mixed solution obtained in step a is subjected to a constant temperature reaction, and after the reaction is completed, it is cooled to room temperature, centrifuged, washed, and vacuum dried to obtain a MOF-activated carbon composite adsorbent.

3. The method for preparing the MOF-activated carbon composite adsorbent according to claim 2, characterized in that: In step a, the molar ratio of ZrCl4 to activated carbon is 1:30-130.

4. The method for preparing the MOF-activated carbon composite adsorbent according to claim 2, characterized in that: In step a, the molar ratio of ZrCl4, water, benzoic acid, organic ligand and DMF is 1:3:10:1:

300.

5. The method for preparing the MOF-activated carbon composite adsorbent according to claim 2 or 4, characterized in that: The organic ligands include terephthalic acid and 2-aminoterephthalic acid.

6. The method for preparing the MOF-activated carbon composite adsorbent according to claim 2, characterized in that: In step b, the isothermal reaction temperature is 80-140° C., and the reaction time is 12-36 h.

7. The method for preparing the MOF-activated carbon composite adsorbent according to claim 2, characterized in that: In step b, the solvents used for washing include DMF, isopropanol and deionized water.

8. The method for preparing the MOF-activated carbon composite adsorbent according to claim 2, characterized in that: In step b, the vacuum drying temperature is 60-100°C.

9. A MOF-activated carbon composite adsorbent for treating ethyl formate, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the MOF-activated carbon composite adsorbent for treating ethyl formate according to claim 9 in the production of brewed food.